Pregnant women’s knowledge of Tetanus disease and immunization against Tetanus disease in the City of Baghdad - Ishraq Ahmed Chiad,; Ban Yousif Yaaqoob, (Journal of the Pakistan Medical Association, 2023)
Objective: To estimate the understanding of tetanus and tetanus toxoid injections among pregnant women. Method: The cross-sectional study was conducted at the Baghdad General Hospital and a primary healthcare centre in Bab-Almuadham, Iraq, from November 15, 2020, to January 15, 2021, and comprised 100 pregnant women aged 15-45 years. Data was gathered through face-to-face structured interviews using a complete self-assessment questionnaire. Data was analysed using SPSS 27. Results: Of the 100 women with mean age of 28.4±10.6 years (range: 15-44 years), 27(27%) were aged 20-24 years, 70(70%) were from the urban areas, 40(40%) had primary education, 69(69%) were housewives, and 85(85%) had had full or partial tetanus toxoid vaccine doses. With respect to knowledge about tetanus disease, 60(60%) subjects answered correctly that tetanus is a serious disease, 52(52%) knew that tetanus infection could also kill the foetus, and 30(30%) recognised that tetanus produces significant side effects. Besides, 80(80%) women considered the vaccine a necessity, and the most common source of information about tetanus vaccination was the health authorities 76(76%). Conclusion: The pregnant women studied were found to have an acceptable level of knowledge about tetanus and tetanus toxoid immunisation. Keywords: Pregnancy, Tetanus, Clostridium tetani, Asymptomatic infections, Tetanus toxoid, Nervous system, Demography, Uterus, Foetus